Developing supplementary reading materials to improve reading comprehension for grade 10th students at a high school in Bac Ninh province - Cao, Thị Thắm (2020)
This thesis reports the findings of an action researchstudyto improve reading skill for grade 10studentsat a high schoolin Bac Ninh province. It attempts to find students‟ opinions of the current textbook, theirdifficulties in learning reading skill in order to provide suitable supplementary reading materialsto improve students‟ reading competence. The data was collected via questionnaireswith 40 students at a high schoolin Bac Ninh province, diagnostic and final testand classroom‟s observation. The findings of this study have shown that most of the students find the reading texts in thecurrent textbookinteresting and relevant with suitable reading tasks. However, they find it hard to improve their reading skillsbecause they lacked reading strategies and suitable supplementary reading materials. Theresearch also gave some suggestions in suitable reading materials and reading strategiesto helpthestudents improve their reading comprehension. Surprisingly, her students make great progress in reading skillsafter the supplementationtime